What Happened to Manufacturing Sector in Industrial Countries? - Aksoy, M. Ataman; Ng, Francis (Advances in Social Sciences Research Journal, 2025)
There has been a relative decline in the manufacturing sectors of industrial countries called "deindustrialization" which consists of the decline in manufacturing employment, trade deficits, factory closings and the decline in the share of manufacturing in GDP. This study analyzes the behavior of growth in selected industrial countries, The USA, UK, France, Italy, Spain, Sweden, Japan, and the Republic of Korea, for the period 1970-2015. The findings of the study show that serious decline of manufacturing apply to very few countries and is caused primarily by high technical change leading to lower manufacturing product prices. This leads to lower incomes for labor and capital and distorts the relative share of manufacturing in GDP.